PROSEDUR PERHITUNGAN DAN PEMOTONGAN PAJAK PENGHASILAN PASAL 21 ATAS PENGHASILAN PENSIUNAN PADA PT TASPEN (PERSERO) CABANG JAMBI - sudibyo, M.; Olimsar , Fredy (Jambi Accounting Review (JAR), 2026)
This study aims to identify and understand the procedures for calculating and withholding Income Tax Article 21 (PPh 21) on pension income at PT Taspen (Persero) Jambi Branch, as well as to analyze the obstacles encountered in its implementation. The research method used is a descriptive method with a qualitative approach, utilizing primary and secondary data obtained through observation, interviews, and literature review. The results indicate that the procedures for calculating and withholding PPh 21 have been carried out in accordance with applicable tax regulations, using both the conventional method and the Average Effective Rate (TER) method as regulated in PMK No. 168 of 2023. The process includes collecting pensioner data, determining gross income, calculating net income, deducting non-taxable income (PTKP), and determining the tax payable followed by tax withholding.